Analysis of Microbolometer Characteristics for Antenna-Coupled Terahertz Detectors - Tiwari1, Ajay; Satoh1, Hiroaki; Aoki2, Makoto; Takeda2, Masanori; Hiromoto2, Norihisa; Inokawa1, Hiroshi (Asian Journal of Chemistry, 2013)
Assuming the use in antenna-coupled bolometers to detect terahertz wave, an integrated heater and thermistor was fabricated with titanium on a silicon substrate and its responsivity was investigated at room temperature. To establish the correlation of microbolometer's responsivity on the properties of its thermistor and heater, an electro-thermal simulation was carried out for the resistance increase with current in thermally isolated heater and resultant increase of temperature. The behaviour of the heater resistance could be reproduced by the simulation successfully. The experimental responsivity shows opposite behaviour from the expected trend. This discrepancy was also explained by simulation and it was concluded that microbolometer with longer heater showed smaller responsivity due to the slower response for the measurement frequency.